Potency of the Endophytic Fungi Cheatomum globosum and Trichoderma harzianum in Resisting the Pathogenic Fungus Alternaria solani That Causes Leaf Spot in Tomato Plants - Mahmood O.Jaafer (University of Thi-Qar Journal of agricultural research, 2024)
Alternaria solani responsible for leaf spot in tomato  is widespread notably